Methylation of miRNA genes in the response to temperature stress in Populus simonii - Ci, Dong; Song, Yuepeng; Tian, Min; Zhang, Deqiang (Frontiers in Plant Science, 2015)
DNA methylation and miRNAs provide crucial regulation for of the transcriptional and post-transcriptional responses to abiotic stress. In this study, we used methylation-sensitive amplification polymorphisms to identify 1066 sites that were differentially methylated in response to temperature stress in Populus simonii. Among these loci, BLAST searches of miRBase identified seven miRNA genes. Expression analysis by quantitative real-time PCR suggested that the methylation pattern of these miRNA genes probably influences their expression. Annotation of these miRNA genes in the sequenced genome of P. trichocarpa found three target genes (homologs of Potri.007G090400, Potri.014G042200, and Potri.010G176000) for the miRNAs produced from five genes (Ptc-MIR396e and g, Ptc-MIR156i and j, and Ptc-MIR390c) respectively. The products of these target genes function in lipid metabolism to deplete lipid peroxide. We also constructed a network based on the interactions between DNA methylation and miRNAs, miRNAs and target genes, and the products of target genes and the metabolic factors that they affect, including(CAT, H2O2, SOD, and lipid peroxide). When plants encounter abiotic stress, they produce signals involving H2O2, malondialdehyde, catalase (CAT), and superoxide dismutase (SOD). The Our results suggested that DNA methylation probably regulates the expression of miRNA genes, thus affecting expression of their target genes, likely through the gene-silencing function of miRNAs, to maintain cell survival under abiotic stress conditions.